QTL analysis of tuber shape in a diploid potato population - Huang, Wei; Dong, Jianke; Zhao, Xijuan; Zhao, Zhiyuan; Li, Chunyan; Li, Jingcai; Song, Botao (Frontiers in Plant Science, 2022)
Tuber shape is one of the most important traits for potato breeding. Since poor or irregular shape increases the difficulty of handling and processing, researching the inheritance of potato tuber shape for potato breeding is highly important. To efficiently identify QTL for tuber shape, a diploid potato population (PM7) was generated by self-pollinated M6 (S. chacoense). The QTL-seq approach was employed to identify a QTL TScha6 for tuber shape at 50.91-59.93 Mb on chromosome 6 in the potato DM reference genome. To confirm TScha6, four SSR and twenty CAPS markers around the QTL were developed and the TScha6 was narrowed down to an interval of ~ 1.85 Mb. The CAPS marker C6-58.27_665 linked to TScha6 was then used to screen 86 potato cultivars and advanced breeding lines. The tuber length/width (LW) ratio was significantly correlated with the presence/absence of C6-58.27_665, and the correlation coefficient was r = 0.55 (p < 0.01). These results showed that C6-58.27_665 could be applied in marker-assisted selection (MAS) for tuber shape breeding in the future. Our research sets the important stage for the future cloning of the tuber shape gene and utilities of the marker in the breeding program.